Sintesis Ramah Lingkungan Senyawa Imina Turunan Vanilin dan 2-Hidroksi Asetofenon Serta Uji Aktivitas Biologi dan Antioksidan - Cahyana, Herry; Pratiwi, Putri (UI Scholars Hub, 2015)
Eco-friendly synthesis of imine derivative compound from 2-hydroxy acetophenone and vanillin had been conducted by using a method of stirring (with stirrer) in a water solvent. The whole experiment began with the synthesis of imine compounds, followed by purification and characterization of the synthesis products and finally analysis on their biological and antioxidant activities. The experiments showed that imine compounds could be synthesized by a chemical reaction of 4-amino antipirin aqueous solution with 2-hydroxy acetophenone and vanillin at magnetic stirrer speed of 250 and 450 rpm, respectively, which produced product A, (E)-4-(1-(2-hydroxyphenyl) ethylideneamino)-1,5-dimethyl-2-phenyl-1H-pyrazol-3(2H) -one and product B, (E)-4-(4-hydroxy-3-(vinyloxy) benzylideneamino)-1,5-dimethyl-2-phenyl-1H-pyrazol-3(2H)-one. Yield percentage (%) obtained from the synthesis of product A and B were 40.68% and 19.76% respectively. Toxicity and antioxidant activity tests showed that the product B were toxic and more active as an antioxidant than product A. While the antibacterial activity test showed that both products had a response to Staphyllococcus aureus bacteria and Escherechia coli bacteria.